2014
DOI: 10.3109/0886022x.2014.949764
|View full text |Cite
|
Sign up to set email alerts
|

Urinary netrin-1 and KIM-1 as early biomarkers for septic acute kidney injury

Abstract: Background: Acute kidney injury (AKI) during sepsis is associated with poor outcome. However, diagnosis of AKI with serum creatinine (SCr) level change is neither highly sensitive nor specific. Therefore, identification of novel biomarkers for early diagnosis of AKI is desirable. Aims: To evaluate the capacity of combining urinary netrin-1 and human kidney injury molecule type 1 (KIM-1) in the early diagnosis of septic AKI. Methods: We prospectively recruited 150 septic patients from Jun 2011 to Jun 2013 at Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 27 publications
0
62
0
6
Order By: Relevance
“…66 In a separate prospective evaluation of 150 septic patients, urinary netrin-1 and kidney injury molecule-1 were increased within 3 hours of admission for patients with AKI. 67 In initial studies, serum NGAL levels showed only marginal prediction for AKI in children with sepsis (AUC, 0.68). A recent study, however, showed the ability of NGAL to improve the prediction of severe AKI afforded by the clinical context model of the renal angina index (AUC increased from 0.72 to 0.84).…”
Section: Sa-aki: How Can Diagnostics and Therapeutics Move Forward Tomentioning
confidence: 99%
“…66 In a separate prospective evaluation of 150 septic patients, urinary netrin-1 and kidney injury molecule-1 were increased within 3 hours of admission for patients with AKI. 67 In initial studies, serum NGAL levels showed only marginal prediction for AKI in children with sepsis (AUC, 0.68). A recent study, however, showed the ability of NGAL to improve the prediction of severe AKI afforded by the clinical context model of the renal angina index (AUC increased from 0.72 to 0.84).…”
Section: Sa-aki: How Can Diagnostics and Therapeutics Move Forward Tomentioning
confidence: 99%
“…In hospitalized patients with AKI, urinary Kim-1 has been shown to predict adverse clinical outcomes such as mortality (29). NGAL is a 25-kDa protein originally isolated from neutrophil secondary granules (30) and is a classic biomarker for the early diagnosis and short-term outcome of AKI.…”
Section: Group a (N=17) Group B (N=21) ------------------------------mentioning
confidence: 99%
“…Current diagnostic criteria for AKI, serum creatinine levels and diuresis, have serious limitations (Khwaja 2012). Diagnostic value of certain novel biomarkers of AKI, neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1), is evident in cardiac surgery (Shao et al 2014;Zhou et al 2015) and sepsis (Tu et al 2014;Dai et al 2015) but not so much in abdominal surgery (Shavit et al 2011;Cullen et al 2014). The quest for new diagnostic biomarkers of AKI remains ongoing.…”
Section: Introductionmentioning
confidence: 99%